(untitled) (Ukrainian Journal of Ophthalmology, 2026)
To assess the efficacy of a combined surgical technique - combined phacoemulsification (phaco) with intraocular lens (IOL) implantation and modified tunnel trabeculopuncture, - in patients with primary open-angle glaucoma (POAG). Materials and Methods: Postoperative intraocular pressure, mean retinal light sensitivity and optical nerve fiber thickness were used as efficacy end points. Conclusion: The combined surgical technique is efficacious for primary open-angle glaucoma from the point of view of normalization of IOP and stabilization in the glaucoma process.